Fraseologia de l’«encara» i processos de gramaticalització - Pérez Saldanya, Manuel; Salvador, Vicent (Caplletra. Revista Internacional de Filologia, 1995)
The main aim of this paper is the study of the processes of grammaticalization involved in the evolution of Catalan concessive encara que from the root (time/aspect) meaning of encara. In the framework provided by the studies of grammaticalization (Traugott, Hopper, etc.), we consider mechanisms of emerging metaphor, strengthening of informativeness, scalar operators, increasing subjectification, and grammaticizacion of discourse strategies, on the basis of the contraexpectative implications of encara. Other usages of encara and some idioms including this word are also considered in the scope of this kind of processes.